2007
DOI: 10.1530/rep-06-0250
|View full text |Cite
|
Sign up to set email alerts
|

A novel pyruvate kinase (PK-S) from boar spermatozoa is localized at the fibrous sheath and the acrosome

Abstract: Boar spermatozoa contain a novel pyruvate kinase (PK-S) that is tightly bound at the acrosome of the sperm head and at the fibrous sheath in the principal piece of the flagellum, while the midpiece contains a soluble pyruvate kinase (PK). PK-S could not be solubilized by detergents, but by trypsin with no loss of activity. Purified PK-S as well as PK-S still bound to cell structures and soluble sperm PK have all kinetics similar to those of rabbit muscle PK-M1. The PK-S subunit had a relative molecular mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…A defective PKM 2 has the potential to create an imbalance in the equilibrium in growth and apoptosis (45,46) thus resulting in growth retardation in BS. Similarly, a defective sperm-specific pyruvate kinase would be unable to maintain normal glycolysis, crucial for sperm mobility (47,48), to explain male-specific infertility in BS. Also, PKM 2 has been reported to interact with microtubules physically (49), with the possibility to affect the motility of microtubule-rich cells like sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…A defective PKM 2 has the potential to create an imbalance in the equilibrium in growth and apoptosis (45,46) thus resulting in growth retardation in BS. Similarly, a defective sperm-specific pyruvate kinase would be unable to maintain normal glycolysis, crucial for sperm mobility (47,48), to explain male-specific infertility in BS. Also, PKM 2 has been reported to interact with microtubules physically (49), with the possibility to affect the motility of microtubule-rich cells like sperm cells.…”
Section: Discussionmentioning
confidence: 99%
“…"Aerobic glycolysis" is known to occur in erythrocytes because these cells do not contain mitochondria [36]. It is also described for sperm where the mitochondria are compartmentalized in the short midpiece of the flagellum and glycolysis may supply the mitochondrial-free region with ATP [37]. Warburg et al observed "aerobic glycolysis" in various tumours (Warburg effect) and believed that an impairment of mitochondrial function caused "aerobic glycolysis" [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that PK was localized in the acrosomal area and the midpiece, while LDH was expressed in the tail. The observations were in according with Feiden et al [36] in boar sperm and Burgos et al [37] in mouse sperm. Exposure goat sperm to AICAR or Met enhanced activity of PK and LDH, while Compound C inhibited activity of both PK and LDH ( Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 95%